Factors Employee Performance with Compensation as Moderating Variables - Yuli Waluyo, Sugeng Eko; Efendi, Mohamad Johan; Huda, Khasbulloh; Sholeh, Rachmad (LPPM of NAROTAMA UNIVERSITY, 2024)
Purpose: The purpose of this study is to investigate the relationship between employee performance and human resource development as well as views of organizational support, with remuneration serving as a moderating factor in the assessment of this relationship. Design/methodology/approach: The investigation will be carried out at PT. International Chemical Industry for the purpose of conducting a case study. Two models are generated by the PLS analysis, which are referred to as the outer model and the inner model. A bootstrapping scenario was used to test the hypothesis, and the results of the t test (t-statistics) were used to interpret the data. PT. International Chemical Industry, which is based in Surabaya, was the location where the research was carried out. Findings: Based on these data, it can be concluded that improvement in human resource management has a favorable and significant impact on employee performance. Based on these data, it can be concluded that the perception of organizational support does not have a positive or statistically significant impact on the performance of employees. Based on these findings, it appears that the provision of money does not have a positive or statistically significant impact on the performance of any employees. According to the findings of this study, human resource development has a considerable detrimental influence on employee performance, which is compensated by increases in wage. The data presented here demonstrates that when salary is taken into consideration, perceived organizational support does not have a statistically significant positive impact on the performance of employees. Practical implications: The findings of this study underline the significance of aligning compensation with the capabilities of employees in order to increase both level of productivity and motivation. It underlines the necessity for organizations to prioritize fair compensation and give sufficient managerial assistance for employee happiness and performance improvement.